Three-dimensional Fusion Imaging without Contrast Medium for Carotid Endarterectomy - Matsumoto, Masaki; Mizutani, Tohru; Sumi, Kenji; Shimizu, Katsuyoshi (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Carotid endarterectomy (CEA) is a popular surgical procedure for patients with carotid artery stenosis. Before performing CEA, radiologic information about carotid artery stenosis must be obtained using three-dimensional (3D) computed tomography angiography (CTA). However, it is difficult to perform 3D-CTA in patients with renal dysfunction and an allergy to contrast medium. To solve this problem, 3D fusion images (3D-FI) with magnetic resonance angiography and 3D computed tomography are created. In this report, we describe the utility of 3D-FI.
Keywords: CEA; contrast medium; three-dimensional fusion images